Pelatihan Pembuatan Sablon Kaos Manual Bagi Remaja Putus Sekolah di Kelurahan Kota Baru Distrik Abepura Kota Jayapura - Mamoribo, Margaretha G.M.I (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This service was carried out in Kota Baru Village, Abepura District, Jayapura City, especially for out-of-school teenagers in Kota Baru Village, Abepura District. The aim of this service is to provide manual T-shirt screen printing training for out-of-school teenagers in Kota Baru sub-district in Abepura District. This is related to providing training and reducing unemployment as well as opening up employment opportunities for out-of-school teenagers in Kota Baru sub-district, Abepura District. This is intended so that students who have dropped out of school will have screen printing skills and get employment opportunities so that they can reduce the number of unemployed in Kota Baru Village, Abepura District. The output of this service is to provide understanding to partners and can become a forum for accommodating every aspiration of students who have dropped out of school in Kota Baru Village so that students who have dropped out of school can still get existing employment opportunities and gain skills for themselves and others, with this training. can be a good step in helping teenagers who have dropped out of school to continue carrying out their activities every day by implementing the screen printing skills they have.